Literature Review: Analysis of Potential Work Accidents in Construction Projects Using the Hazard Identification, Risk Assessment, and Risk Control Method - Magda, Salmina; Yustiarini, Dewi; Nurasiyah, Siti (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Along with advances in science and technology, the development of the building sector is also increasing. Multi-storey buildings are an alternative to meet the needs of big cities with very limited land. The rapid development of construction project development, in addition to providing benefits, can also cause the risk of accidents that can cause disruption or cessation of project work activities. The literature review aims to review the potential for work accidents and risk assessments on construction projects. A literature review is based on issues, methodologies, similarities and research proposals. Based on the result of 8 studies, it was found that the high-risk category is the risk of falling from a height, workers buried by avalanches during excavation work, the risk of being hit by material, and being electrocuted during excavation work with tools and equipment accidents. Based on the identification and assessment, it was found that the work of the upper structure has more risk, and the average risk index is greater than that of the lower structure.